Marking Physical Literacy or Missing the Mark on Physical Literacy? A Conceptual Critique of Canada's Physical Literacy Assessment Instruments. Issue 1 (2nd January 2017) - Robinson, Daniel B.; Randall, Lynn
ABSTRACT: Margaret Whitehead first introduced the concept of physical literacy over 20 years ago. Since that introduction, physical literacy has been gaining in popularity within many Western physical education and sport contexts. This is particularly true within Canada, where physical literacy has been embraced by two of the nation's most notable national physical education and sport organizations (i.e., Physical and Health Education Canada, Canadian Sport for Life). As physical literacy has been generating interest and action by these organizations, they, and others, have been quick to also seek methods by which to measure it. However, it is our observation that despite the promises and possibilities of physical literacy resources, initiatives, and programs, Canada's most accessible physical literacy assessment instruments are wanting for focused and direct contemplation. In this article, we offer a conceptual critique of the physical literacy assessment instruments being developed for and practices being encouraged within Canadian school communities. Our contemplations consider three physical literacy assessment instruments, and they are focused, principally, upon usability, trustworthiness, and fidelity to Whitehead's conception of physical literacy. We conclude that the instruments differ in their ease of use and usefulness, some are lacking, markedly, with respect to trustworthiness, and some fail to capture physical literacy as Whitehead intended it. Finally, in light of these conclusions, we offer suggestions for future practice and inquiry.